Draft genome sequence of Paenibacillus dauci sp. nov., a carrot-associated endophytic actinobacteria - Qian Wu (Genomics Data, 2015)
Paenibacillus dauci sp. nov., a new kind of endophytic actinobacteria, is separated from the inner tissues of carrot sample, which forms intimated associations with carrot acting as biological control agents. Here we report a 5.37-Mb assembly of its genome sequence and other useful information, including the coding sequences (CDSs) responsible for biological processes such as antibiotic metabolic process, antimicrobial metabolism, anaerobic regulation and the biosynthesis of vitamin B and polysaccharide. This novel strain can be a potential source of novel lead products for exploitation in the field of pharmaceutical, agriculture and industry.